Linking property rights and capital accumulation in the Philippines - Velasco, Mark Anthony M. (Animo Repository, 2014)
This study investigates the link between property rights and capital accumulation in the context of poverty alleviation in the Philippines. Property rights are represented by the provision of land titles to those informal settlers while capital accumulation is concretely manifested through access to credit. The study focuses on explaining how provisions of land titles to the poor affect their access to credit and therefore improvement in life conditions. A former community of informal settlers in the City of Taguig, Philippines was chosen in the study to shed evidence using a case study design. Remarkably, the results signify notable relationship between the provisions of land titles and improved life conditions among the poor. © 2014 by De La Salle University, Philippines.